Hyperhydration-induced decrease in urinary luteinizing hormone concentrations of male athletes in doping control analysis - Athanasiadou, I.; Voss, S. C.; El Saftawy, W.; Al-Jaber, H.; Dbes, N.; Al-Yazedi, S.; Samsam, W.; Mohamed-Ali, V.; Alsayrafi, M.; Valsami, G.; Georgakopoulos, C. (International Journal of Sport Nutrition and Exercise Metabolism, 2019)
Low urinary luteinizing hormone (LH) values have been discussed as a marker to detect steroid abuse. However, suppressed LH concentrations related to highly diluted urine samples could be a misleading indication of anabolic steroid abuse. One aim of the present study was to examine the effect of hyperhydration on the interpretation of LH findings during doping control analysis and to investigate different possibilities to correct volume-related changes in urinary LH concentrations. Seven healthy, physically active, nonsmoking White males were examined for a 72-hr period, using water and a commercial sports drink as hyperhydration agents (20 ml/kg body weight). Urine samples were collected and analyzed according to the World Anti-Doping Agency`s technical documents. Baseline urinary LH concentrations, expressed as the mean ± SD for each individual, were within the acceptable physiological range (7.11 ± 5.42 IU/L). A comparison of the measured LH values for both hyperhydration phases (Phase A: 4.24 ± 5.60 IU/L and Phase B: 4.74 ± 4.72 IU/L) with the baseline ("normal") values showed significant differences (Phase A: p < .001 and Phase B: p < .001), suggesting the clear effect of urine dilution due to hyperhydration. However, an adjustment of urinary LH concentrations by specific gravity based on a reference value of 1.020 seems to adequately correct the hyperhydration-induced decrease on the LH levels